(untitled) (Terr@ Plural, 2021)
Episodes of precipitation are part of the climate variability of a region; however, when associated with impermeability processes of the soils and inefficient urban drainage, they increase the rates of floods and overflows events, which cause severe inconvenience and damage for the population. Thus, this study correlates the record of 60 occurrences of floods and overflows, in the Ronda stream watershed, located largely in the urban area of the city of Ponta Grossa, between the years 1980 and 2017. Half of the occurrences happened due to extreme events, that is, with precipitation equal to or greater than 50 mm. Many occurrences occurred in areas considered to be at risk, mainly in the floodplain of the Ronda stream.